Quantifying the impact of sulfate geoengineering on mortality from air quality and UV-B exposure. (August 2018) - Eastham, Sebastian D.; Weisenstein, Debra K.; Keith, David W.; Barrett, Steven R.H.
Abstract: Sulfate geoengineering is a proposed method to partially counteract the global radiative forcing from accumulated greenhouse gases, potentially mitigating some impacts of climate change. While likely to be effective in slowing increases in average temperatures and extreme precipitation, there are known side-effects and potential unintended consequences which have not been quantified. One such consequence is the direct human health impact. Given the significant uncertainties, we take a sensitivity approach to explore the mechanisms and range of potential impacts. Using a chemistry-transport model, we quantify the steady-state response of three public health risks to 1 °C global mean surface cooling. We separate impacts into those which are "radiative forcing-driven", associated with climate change "reversal" through modification of global radiative forcing, and those "direct impacts" associated uniquely with using sulfate geoengineering to achieve this. We find that the direct (non-radiative forcing driven) impact is a decrease in global mortality of ∼13, 000 annually. Here the benefits of reduced ozone exposure exceed increases in mortality due to UV and particulate matter, as each unit of injected sulfur incurs 1/25th the particulate matter exposure of a unit of sulfur emitted from surface sources. This reduction is exceeded by radiative forcing-driven health impacts resulting from using sulfate geoengineering to offset 1 °C of surface temperature rise. Increased particulate matter formation at these lower temperatures results in ∼39, 000 mortalities which would have been avoided at higher temperatures. As such we estimate that sulfate geoengineering in 2040 would cause ∼26, 000 (95% interval: −30, 000 to +79, 000) early deaths annually relative to the same year without geoengineering, largely due to the loss of health benefits associated with CO2 -induced warming. These results account only for impacts due to changes in air quality and UV-B flux. They do not account for non-mortality impacts or changes in atmospheric dynamics, and must be considered in the wider context of other climate change impacts such as heatwave frequency and sea level rise. Highlights: Direct, non-climate effects of sulfate injection produce net health risk reduction. Surface sulfur emission incurs 25 times the exposure from stratospheric injection. Disbeneficial climate change-driven health effects dominate impacts of injection. Net impacts of injection harmful despite beneficial photochemical response. Injection health impacts small relative to risks associated with climate change.